Distribution of tumor-infiltrating immune cells in glioblastoma - Orrego Puelles, Enrique, (2018)
Aim: Evaluation of features related to infiltrating immune cell level in glioblastoma. Methods: Tumor-infiltrating lymphocytes (TILs) through H&E staining, and TILs (CD3, CD4, CD8 and CD20) and macrophage (CD68 and CD163) levels through immunohistochemistry were evaluated through digital analysis. Results: CD68 (9.1%), CD163 (2.2%), CD3 (1.6%) and CD8 (1.6%) had the highest density. Higher CD4+ was associated with unmethylated MGMT (p = 0.016). Higher CD8+ was associated with larger tumoral size (p = 0.027). Higher CD163+ was associated with higher age (p = 0.044) and recursive partitioning analysis = 4. Women (p < 0.05), total resection (p < 0.05), MGMT-methylation (p < 0.001), radiotherapy (p < 0.001), chemotherapy (p < 0.001) and lower CD4+ (p < 0.05) were associated with longer overall survival. Conclusion: Macrophages are more frequent than TILs. Some subsets are associated with clinical features.